Growth-Inhibitory Effect of d-Tryptophan on Vibrio spp. in Shucked and Live Oysters - Chen, Jian (Appl Environ Microbiol, 2018)
Vibrio vulnificus and Vibrio parahaemolyticus are important human pathogens that are frequently transmitted via consumption of contaminated raw oysters. A small amount of d-tryptophan (d-Trp) inhibits some foodborne pathogenic bacteria in high-salt environments. In this study, we aimed to evaluate the antibacterial effect of d-Trp on V. vulnificus and V. parahaemolyticus in culture media, artificial seawater, and shucked and live oysters. The effectiveness of d-Trp in growth inhibition of Vibrio spp. was highly dependent on environmental NaCl concentrations. Higher levels of NaCl (>4.0%) with d-Trp (>20 mM) resulted in higher and more consistent growth inhibition of both Vibrio spp. Treatment with 40 mM d-Trp significantly (P < 0.05) reduced viable V. parahaemolyticus cell counts in tryptic soy broth (TSB) with >4.0% NaCl at 25°C. In contrast, V. vulnificus was more sensitive to d-Trp (20 mM) than V. parahaemolyticus. d-Trp (40 mM) treatment with NaCl (>4.5%) significantly (P < 0.05) inhibited the growth of V. parahaemolyticus and V. vulnificus in shucked oysters immersed in peptone water at 25°C throughout a 48-h incubation period. In artificial seawater, d-Trp exhibited a stronger growth-inhibitory effect on V. vulnificus and V. parahaemolyticus at 25°C than in TSB at the same level of salinity and inhibited the growth of both V. parahaemolyticus and V. vulnificus in live oysters at 25°C for 48 h. Furthermore, we tested the synergistic effect of d-Trp and salinity on the inhibition of total viable bacterial counts (TVC) at refrigeration temperature. d-Trp (40 mM) inhibited the growth of TVC in shucked oysters immersed in artificial seawater at 4°C. Therefore, these results revealed that d-Trp will serve as a novel and alternative food preservative to control Vibrio spp. in live oysters at ambient temperature and to extend the shelf-life of shucked oysters at refrigeration temperature. IMPORTANCE Oysters are the primary transmission vehicles for human Vibrio infections. Raw oyster consumption is frequently associated with gastroenteritis. The current postharvest methods, such as high-pressure processing, used to control Vibrio spp. in fresh oysters are still insufficient because of limited facilities, high cost, and potential adverse effects on production. We demonstrate that adding a small amount of d-tryptophan (d-Trp) inhibits the growths of Vibrio parahaemolyticus and Vibrio vulnificus in a high-salt environment at even ambient temperature. We further investigated the d-Trp treatment conditions and clarified the relationship between salt and d-Trp concentrations for optimal growth-inhibitory effect of Vibrio spp. The results will be useful for enhancing the effectiveness of d-Trp by increasing salinity levels. Furthermore, in a nutrientfree environment (artificial seawater), a stronger inhibitory effect could be observed at relatively lower salinity levels, indicating that d-Trp may be regarded as effective food preservation in terms of salinity reduction. Therefore, we suggest the use of exogenous d-Trp in a seawater environment as a novel and effective strategy not only for controlling Vibrio in live oysters at even ambient temperature but also for effectively retarding spoilage bacterial growth and extending the shelf life of shucked oysters at refrigeration temperature.